2019
DOI: 10.2174/0929867326666190603123838
|View full text |Cite
|
Sign up to set email alerts
|

Periphery Decorated and Core Initiated Neutral and Polyanionic Borane Large Molecules: Forthcoming and Promising Properties for Medicinal Applications

Abstract: A mini-review based on radial growing macromolecules and core initiated Borane periphery decorated with o-carboranes and metallacarboranes that has been developed in the authors laboratories is reported. The review is divided into four sections; three of them are related to the design and synthesis of these large boron-containing molecules and the fourth deals with the unique properties of anionic metallacarborane molecules that provide a glimpse of their potential for their promising use in medicinal applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 104 publications
(115 reference statements)
0
20
0
Order By: Relevance
“…These complexes may serve as boron sources for BNCT [35,36]. In addition, boron clusters and their conjugates with nucleosides exhibit high binding affinity for plasma proteins under in vitro and in vivo conditions [37,38] as well as the ability to cross bilayer membranes and to interact with cell membranes [39]. Recently, it was shown that a conjugate of cobalt bis(1,2-dicarbollide) and a Tβ4 protein (thymosin β4) incubated with cardiomyocytes increased the viability of hypoxic rat heart cells [40] and enhanced the wound healing potential of Tβ4 in human fibroblasts [41].…”
Section: Discussionmentioning
confidence: 99%
“…These complexes may serve as boron sources for BNCT [35,36]. In addition, boron clusters and their conjugates with nucleosides exhibit high binding affinity for plasma proteins under in vitro and in vivo conditions [37,38] as well as the ability to cross bilayer membranes and to interact with cell membranes [39]. Recently, it was shown that a conjugate of cobalt bis(1,2-dicarbollide) and a Tβ4 protein (thymosin β4) incubated with cardiomyocytes increased the viability of hypoxic rat heart cells [40] and enhanced the wound healing potential of Tβ4 in human fibroblasts [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinically used boron compounds, such as boronophenylalanine (BPA) and sodium borocaptate (BSH) exhibit low cellular uptake, low boron content, limited permeability across the brain‐blood barrier (BBB) hampered its application for effective tumor BNCT [3] . To solve those problems, different kinds of nanomaterials including emulsions, [4] liposomes, [5] dendrimers, [6] graphene‐based systems, [7] quantum dots, [8, 9] carbon nanotubes, [10, 11] and gold nanoclusters [12] have been conjugated to 10 B enriched compounds as smart cargoes [13] . Nonetheless, on average, only 0.7 % of the NPs introduced in a patient's body reach the tumor [14] .…”
Section: Methodsmentioning
confidence: 99%
“…[3] To solve those problems, different kinds of nanomaterials including emulsions, [4] liposomes, [5] dendrimers, [6] graphenebased systems, [7] quantum dots, [8,9] carbon nanotubes, [10,11] and gold nanoclusters [12] have been conjugatedt o 10 Be nriched compounds as smart cargoes. [13] Nonetheless, on average, only 0.7 %o ft he NPs introduced in ap atient's body reach the tumor. [14] Poor permeability of the blood-brain barrier andsubsequent rapid clearance from blood circulation by the reticuloendothelial system are major problems for brain drug delivery systems.…”
mentioning
confidence: 99%
“…There are only limited examples of poly­(nano-ions) in the literature. Examples of smaller structures (unique oligomers and dendrimers) based on carborane and metallacarborane clusters have been synthesized in the laboratories of Hosmane, Teixidor, and Núñez. Furthermore, Uchman and collaborators studied triblock terpolymer micelles containing short blocks (ca. five units) with attached ortho -carborane moieties, which were transformed to ionic nido -carboranes …”
Section: Introductionmentioning
confidence: 99%